Tafāḋul al-Umam fī al-Qur’ān al-Karīm - Selim, Noha Kamal (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This study aims to analyze the concept of differentiation, "Tafāḋul," one of the concepts of divine law in the Qur'an. This research is qualitative and uses a type of literature study. This research uses a semantic approach. The research data is in the form of the concept of differentiation "Tafāḋul" with the source of Qur'an data. The data collection technique uses documentation. Meanwhile, data analysis uses content analysis. The results of the study show that the concept of "al-Sunan Alelahia" divine laws refers to the divine laws governing history and nations. Differentiation between individuals and nations is a law established by God Almighty in the universe to enhance competition and effectiveness between humans to obtain the higher degrees of Paradise, and the divine preference for humans over all other creatures is The most comprehensive circle of preference is followed by the preference for those who carry messages, followed by the preference of nations over each other, and the preference for some groups of society, such as the preference for those who fight with their money and their lives over those who remain idle, that is, the preference for those with high determination over those who are passive and idle. So preference is for the one who carries out the message and advances the nation and elevates it. During the research, I explained the characteristics of the best nation and its descriptions in the Holy Qur’an, and how these characteristics are constant over time, deriving their stability from divine laws, but the best nations change over time according to their firmness and commitment to the divine commandments and their fulfillment of the charitable role assigned to them. If they regress and deviate from the path of righteousness, their fate is to disappear.